Recommendations for coastal planning and beach management in Caribbean insular states during and after the COVID19 pandemic (2021)
The COVID-19 pandemic has implications for coastal planning and management. Rules for isolation and physical distancing, among other measures for human life protection, have led to the closure of most beaches around the world. The present critical situation has raised the following question: How can some recommendations be designed in sun, sea, and sand tourism-dependent-insular countries to face “the COVID-19 new normality?” We used the content analysis technique to analyze representative publications on a global level to ascertain information on best management practices. A survey of 58 experts provided additional information. We used inferential statistics for sample selection and produced a list of 43 practices and beach planning and management actions to face the COVID-19 pandemic. This led to 27 new recommendations designed for beach planning and management within insular contexts, some of which were tested in the Republic of Cuba. Recommendations aim to guarantee a culture of safety and improvement within the field of beach or coastal planning and management. These recommendations should prove useful for other insular countries, during the COVID-19 period, in the new normality that follows, and in other post-pandemic scenarios.